International Activity of the Universitites - A. V. Barsukova; I. I. Zhukovskiy (Vestnik MGIMO-Universiteta)
International cooperation in Academia became a norm. The evolution from sporadic contacts of leading professors for academic and scientific relations to wide cooperation programmes basing on a common values and political mission and aiming to the attraction of human recourses on external markets took a moderate period of time according to the history. Why European Universities cooperate? What are the tasks for cooperation with third countries? How the vector of cooperation between universities systems between Russia and EU have been developin?